An empirical analysis of learning styles and generic competencies in university students: case of health services administration students in the city of Barranquilla, Colombia (2024)
The objective of the study is to determine the relationship between learning styles and the development of generic competencies in Health Services Administration students; through a correlational study, in a population of 170 Health Services Administration students in the city of Barranquilla. For learning styles, Kolb's learning styles instrument was used; and for generic competencies, a standardized test designed under the methodology of the Evidence-Based Model and oriented to monitor the development of critical reading, written communication, citizenship competencies, quantitative reasoning and English. The resulting data were organized in a spreadsheet and processed using Statgraphics and R software. The results show that there is a strong relationship between divergent style and written communication, resulting from diversity in their concrete and reflective approach.